2014
DOI: 10.1186/1477-7819-12-170
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pathological complete response to neoadjuvant chemoradiotherapy for esophageal squamous cell carcinoma

Abstract: BackgroundsIn this study, we evaluated the factors associated with a pathologic complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) for esophageal squamous cell carcinoma (ESCC).MethodsPre-nCRT parameters in ESCC patients treated between 1999 and 2006 were analyzed to identify predictors of pCR. All patients received 5-fluorouracil/cisplatin-based chemotherapy and external beam radiation followed by scheduled esophagectomy. Variables were analyzed using univariate and multivariate analyses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…The pathCR rate was 24% (23% and 32% for patients with AC and SCC, respectively). These results are in accordance with published reports on this subject, in which the pathCR rate has ranged from 19% to 30%, with AC patients achieving a lower pathCR rate than SCC patients, for whom the pathCR rates are slightly higher (Table ). A recently published report by Chao et al from the Taiwan Cancer Registry showed a 28.9% pathCR rate among 1103 patients with esophageal SCC.…”
Section: Discussionsupporting
confidence: 92%
“…The pathCR rate was 24% (23% and 32% for patients with AC and SCC, respectively). These results are in accordance with published reports on this subject, in which the pathCR rate has ranged from 19% to 30%, with AC patients achieving a lower pathCR rate than SCC patients, for whom the pathCR rates are slightly higher (Table ). A recently published report by Chao et al from the Taiwan Cancer Registry showed a 28.9% pathCR rate among 1103 patients with esophageal SCC.…”
Section: Discussionsupporting
confidence: 92%
“…The reported influences of clinical parameters-including pretreatment EUS-based tumor length and T stage and posttreatment endoscopic biopsy-on the probability of pathCR in our study were in accordance with existing literature (5,40,41). The finding that induction chemotherapy before chemoradiotherapy was associated with a significantly higher rate of pathCR in the current series was in line with a recent phase II randomized trial at MDACC that did report a difference in pathCR rate in favor of induction chemotherapy (26% vs. 13%), but this difference was not statistically significant in that trial (P 5 0.094) (42).…”
Section: Discussionsupporting
confidence: 91%
“…Several reports revealed the survival benefit in pCR cases after neoadjuvant therapy for esophageal cancer and suggested the necessity of a useful predictor of pCR [ 10 , 11 ]. Furthermore, studies have reported some examination methods and biomarkers to predict pCR after neoadjuvant therapy for esophageal cancer, although no predictors of pCR have been developed for clinical application in esophageal cancer [ 43 – 45 ]. A previous study found no significant differences in the oncological outcomes of clinical complete response (cCR) cases between a no treatment group and a radical surgery group after neoadjuvant chemoradiotherapy or radiotherapy for advanced esophageal cancer [ 46 ], and the data suggested a “watch and wait” policy for cases with cCR in order to avoid the morbidity associated with radical surgery.…”
Section: Discussionmentioning
confidence: 99%